Development of communicative competence of future workers - Abdrasilova V.O., Абдрасилова В.О.; Meirbekova J.M., Меирбекова Ж.М. (Рroblems of engineering and professional education, 2023)
One of the main goals of modem Kazakhstan education is the development o f communicative competence o f future specialists. It consists of cognitive, organizational and psychological parts. Formation of these qualities is one of the main problems of training future doctors, the pledge of their personal and professional growth.